Macro stickiness in strategic planning of Malaysia's higher education - Sarif, Suhaimi Mhd (2011)
Purpose: This study aims to investigate the influence of macro stickiness in strategic planning of Malaysia’s higher education. Stickiness is an economic phenomenon in terms of cost, imposed preferences, policy paradigm and national priorities that caused the planning to be inadequate to the response changes with robust and dynamic. The body of knowledge of macro stickiness is derived from the literature in the field of innovation studies, in which governments have been identified as major contributors to macro level stickiness.